PERAN AUDIT EKTERNAL DALAM MEMAJUKAN USAHA KECIL DAN MENENGAH DI JAWA TENGAH: SEBUAH KAJIAN KONSEPTUAL - Suyono, Eko; Rusmana, Oman; SE, Warsidi; Fathurokhman, Agus (Soedirman Accounting, Auditing and Public Sector Journal, 2022)
Small and Medium Enterprises (SMEs) are the backbone of the economy in most countries around the world, including Indonesia. In Central Java, until the end of the fourth Quarter of 2016, there were 115,751 units of SMEs contributing for 791,767 jobs. Some of the weaknesses of SMEs compared to large and modern businesses is the limited financial condition and difficulties faced when it will apply for funding to the bank. It is because SMEs generally are unable to present the financial statements in accordance with the accounting standards as one of lending criteria from the bank. To overcome the problem, the financial statement of SMEs should be audited by the independent auditors. Therefore, the financial statement of SMEs will be more reliable so that the bank will approve SMEs credit application. In another word, the audit for SMEs can be said as one of the ways to overcome the weakness of SMEs so that SMEs will become more bankable